Fitness Assessment, Athlete's Monitoring Cycle and Training Interventions in Team Sports - Clemente, Filipe; Sarmento, Hugo (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Team sports training are progressively growing, and thus challenging strength and conditioning coaches and head coaches. As part of a well-prepared training strategy, it is important to establish a functional relationship among fitness assessment, load, and well-being monitoring and readiness analysis to identify the consequences of training stimulus for players. Each of these topics has already been isolated in research; however, it is important to bridge the gap between them and establish a greater and more comprehensive approach among fitness adaptations, training monitoring, and specific interventions performed. This may help us to achieve a clearer view of the big picture in terms of the consequences for players, such as, considering their exposure to successful biological adaptations or less successful cases, including illness or injuries. As it is clear that more research should be performed on the relationship among these dimensions and topics, the aim of the Special Issue on "Fitness Assessment, Athlete's Monitoring Cycle and Training Interventions in Team Sports" was to publish high-quality original investigations, systematic reviews, and meta-analysis in the research field of team sports. We have published 22 articles that cover the topics of performance assessment and relationships between fitness measures; training load monitoring, well-being, and readiness in team sports;training interventions; complementary strategies for performance (e.g., nutrition, supplementation, psychology, injury preventions, and recovery); and determinants of illness and injuries in players.